Antara “Penderitaan yang Tersisa” dan “Rengkuhan yang Terbuka”: Analisis Teologis atas Trauma Sosial Pascakonflik Ambon: Antara “Penderitaan yang Tersisa” dan “Rengkuhan yang Terbuka”: Analisis Teologis atas Trauma Sosial Pascakonflik Ambon - Patty, Lidya (Sekolah Tinggi Teologi Tawangmangu, 2025)
This article examines the collective trauma of the 1999–2002 Ambon post-conflict, which still leaves traces in the violent events of 2011 and early 2025. These social wounds indicate that the community's collective memory has not fully recovered and remains a source of vulnerability in interfaith relations. This paper aims to develop a trauma-healing-based reconciliation model in the Ambon context. Using qualitative methods based on literature studies, data are analyzed conceptually and thematically through three main approaches: Jeffrey C. Alexander's theory of collective trauma, Shelly Rambo's theology of trauma, and Miroslav Volf's theology of reconciliation. This article puts forward two arguments. First, post-conflict trauma in Ambon is still alive and is indicated by repeated conflicts in 2011 and early 2025 that reactivated the memory of the 1999 violence. Second, formal reconciliation such as the Malino II Agreement has not yet addressed the dimensions of deep trauma recognition and healing. Therefore, this article proposes the formation of a transformative space as a space between